2008
DOI: 10.1002/gcc.20528
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of BCR/ABL1‐dependent transcriptional response reveals enrichment for genes involved in negative feedback regulation

Abstract: Philadelphia (Ph) chromosome-positive leukemia is characterized by the BCR/ABL1 fusion protein that affects a wide range of signal transduction pathways. The knowledge about its downstream target genes is, however, still quite limited. To identify novel BCR/ABL1-regulated genes we used global gene expression profiling of several Ph-positive and Ph-negative cell lines treated with imatinib. Following imatinib treatment, the Ph-positive cells showed decreased growth, viability, and reduced phosphorylation of BCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…These three genes as well as PIM1 act as negative regulators of the JAK-STAT signalling pathway. 28,29 As JAK2V617F causes constitutive activation of the JAK-STAT signalling in haematopoietic cells, 2-5 it consequently activates several negative feedback systems, mainly including members of the SOCS family, which initially might act to suppress the tumour promoting effects of the JAK2V617F oncogene. 30 The activation of the negative feedback of JAK-STAT pathway could explain the higher expression of SOCS2 and SOCS3 detected in JAK2V617F-positive ET.…”
Section: Gene Expression Patterns In Relation To Jak2v617fmentioning
confidence: 99%
See 1 more Smart Citation
“…These three genes as well as PIM1 act as negative regulators of the JAK-STAT signalling pathway. 28,29 As JAK2V617F causes constitutive activation of the JAK-STAT signalling in haematopoietic cells, 2-5 it consequently activates several negative feedback systems, mainly including members of the SOCS family, which initially might act to suppress the tumour promoting effects of the JAK2V617F oncogene. 30 The activation of the negative feedback of JAK-STAT pathway could explain the higher expression of SOCS2 and SOCS3 detected in JAK2V617F-positive ET.…”
Section: Gene Expression Patterns In Relation To Jak2v617fmentioning
confidence: 99%
“…Similarly, a recent study in MPD Philadelphia positive patients has described that BCR/ABL signalling activates several negative feedback regulatory systems (such as JAK-STAT inhibitors). 28 This effect might be overcome by increased BCR/ABL signalling or by signalling via additional or alternative pathways, which subsequently causes an increased signalling in the JAK-STAT pathway. Moreover, Verdier et al 31 described that the overexpression of STAT5 overcomes the inhibitory effects of CISH on erythropoietin signalling.…”
Section: Gene Expression Patterns In Relation To Jak2v617fmentioning
confidence: 99%
“…Regulation of mRNA expression is rapid, suggesting it is a direct response to inhibition of tyrosine kinase-mediated signalling from the BCR-ABL1 protein. Several studies have previously identified many potential BCR-ABL1 target genes but MECOM was not described (Håkansson et al, 2008;Nunoda et al, 2007;Bianchini et al, 2007). This study represents the first report of a signal transduction pathway that regulates MECOM gene expression.…”
Section: Discussionmentioning
confidence: 69%
“…Abelson transformed cells, unlike BCR-Abl transformed cells, exhibit low levels of NF-κB activity; upon v-Abl inhibition, NF-κB activity levels dramatically increase (Hakansson et al, 2008; Klug et al, 1994; Zou and Calame, 1999). Previously, our lab reported that overexpression of the NF-κB subunit RelA is toxic to v-Abl transformed cells, resulting in a 2-3 fold increase in the fraction of apoptotic cells (Sheehy and Schlissel, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Though both BCR-Abl and v-Abl fusion proteins produce leukemias, the signaling pathways initiated by the proteins differ. For example, BCR-Abl-transformed cells have high levels of active NF-κB and little to no ERK activity, while the reverse is true in v-Abl transformed cells (Hakansson et al, 2008; Klug et al, 1994; Zou and Calame, 1999). …”
mentioning
confidence: 99%